Cómo negociar con éxito en 50 países - Olegario Llamazares García-Lomas
Países: Alemania. -Arabia Saudí. -Argentina. -Australia. -Bélgica. -Brasil. -Canadá. -Chile. -China. -Colombia. -Corea del Sur. -Dinamarca. -Ecuador. -Egipto. -España. -Estados Unidos. -Filipinas. -Finlandia. -Francia. -Grecia. -Hungría. -India. -Indonesia. -Irlanda. -Israel. -Italia. -Japón. -Malasia. -Marruecos. -México. -Nigeria. -Países Bajos. -Panamá. -Perú. -Polonia. -Portugal. -Reino Unido. -República Checa. -Rumania. -Rusia. -Singapur. -Sudáfrica. -Suecia. -Suiza. -Tailandia. -Taiwán. -Turquía. -Uruguay. -Venezuela. -Vietnam.